The progressive governments of Latin America in the international context: an approach to their limits - Ugarteche, Oscar (2018)
In the period from 2003 to 2017 progressive governments were elected with a post-neoliberal agenda. Fatigue of reforms, excess of market ideology, little respect for democratic institutions by neoliberal governments, low wages, job insecurity, increase of informal employment, dismantling of unions, and ideological self-assurance in the official media saturated the citizenship. In the middle of the second decade of the 21st century, barely a decade after the progressive parties where elected to government, they began to lose popularity and elections. What is going to be reviewed in the present text is why this happened almost simultaneously, reviewing economic and political variables. In this text we will review some variables of the main economic problems faced and also proceed to review the political problems and their variables. The end is a conclusion about the problems posed by governments that tried to approach progressive policies or the socialism of the XXI century.